Harvesting Renewable Resources of Population with Size Structure and Diffusion - Qiang-Jun Xie; Ze-Rong He; Chun-Guo Zhang (Abstract and Applied Analysis)
The aim of this work is to explore the optimal exploitation way for a biological resources model incorporating individual’s size difference and spatial effects. The existence of a unique nonnegative solution to the state system is shown by means of Banach’s fixed point theorem, and the continuous dependence of the population density with the harvesting effort is given. The optimal harvesting strategy is established via normal cone and adjoint system technique. Some conditions are found to assure that there is only one optimal policy.